2020
DOI: 10.1177/1479164120958425
|View full text |Cite
|
Sign up to set email alerts
|

An optical coherence tomography comparison of coronary arterial plaque calcification in patients with end-stage renal disease and diabetes mellitus

Abstract: Background: Coronary arterial plaques in patients with end-stage renal disease (ESRD) are assumed to have increased calcification due to underlying renal disease or initiation of dialysis. This relationship may be confounded by comorbid type 2 diabetes mellitus (DM). Methods: From a single-center OCT registry, 60 patients were analyzed. Twenty patients with ESRD and diabetes (ESRD-DM) were compared to 2 groups of non-ESRD patients: 20 with and 20 without diabetes. In each patient, one 20 mm segment within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Furthermore, the progression of CAC is more complex in the presence of end-stage renal failure. 23 Our study demonstrated that DM and HD duration are associated with severe CAC, consistent with these reports. In addition, DM control contributes to the progression of CAC.…”
Section: Association Between Dm and Cacsupporting
confidence: 92%
“…Furthermore, the progression of CAC is more complex in the presence of end-stage renal failure. 23 Our study demonstrated that DM and HD duration are associated with severe CAC, consistent with these reports. In addition, DM control contributes to the progression of CAC.…”
Section: Association Between Dm and Cacsupporting
confidence: 92%
“…Diabetes drives the multivessel disease progression and the diffused atherosclerotic plaque with calcium deposits are developed strongly as compared with other TARFs. 25 , 26 In a separate study, plaques in current smokers were found to be more strongly associated with high‐risk plaque, such as low‐attenuation plaques and napkin‐ring sign, as evident in coronary computed tomography angiography when compared with other TARFs. 27 The study using optical coherence tomography and intravascular ultrasound imaging also showed that current smokers had significantly more lipid‐rich plaque, thin‐cap fibroatheroma, and fewer plaques with calcium than former smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 94%